Yield and Quality of Multicut Fodder Sorghum as Affected by Nutrient Levels and Biofertilizer Application - Kushwaha, Manish; Singh, Magan; Kumar, Rakesh; Tyagi, Nitin; Soni, Pooja Gupta; Choudhary, Sunita; Makarana, Govind (Indian Journal of Animal Nutrition, 2018)
A field experiment was carried out to study the effect of nutrient level and biofertilizer on yield and quality of multicut fodder sorghum (Sorghum bicolor L.). The experiment was laid out in split plot design with three multicut fodder sorghum varieties (CSH 20MF, CSH 24MF and CO(FS) 29) in the main plot and five levels of nutrients (Control, N90P40, N90P40 + BF, N60P40 + BF and N30P20 + biofertilizer (BF)) as subplot treatments with three replications. The higher green fodder yield was obtained with CO(FS)29 variety at N90P40 + BF nutrient level. Among the varieties, maximum DM contents (25.34%) and yield (212.76 q/ha) were obtained for variety CO(FS)29 while in respect to nutrient level, the highest DM content (24.74%) and yield (158.44 q/ha) were recorded with N90P40 + BF level of fertilization. The CP and EE level of three cuts was at par with respect to varieties while the maximum yield was found for variety CO(FS)29. The highest CP and EE content (8.37 and 2.37%, respectively) was obtained at N90P40 + BF. Total ash content was higher by 16.93 and 20.38, 62.68% and 56.15% in variety CO(FS)29 over CSH 24MF and CSH 20MF, respectively. Among nutrient levels, higher total ash (10.76%) was estimated at N90P40 + BF level. The total carbohydrate and cell soluble content was recorded highest in control and N90P40 + BF, respectively, While higher NDF and ADF content was estimated in CSH 20MF and CO(FS)29 variety, respectively over control treatment. CO (FS)29 was the most promising because of higher green fodder, dry matter and nutrient yield than CSH 20MF and CSH 24MF.